Prevalence and severity of burnout in Hong Kong doctors up to 20 years post-graduation: a cross-sectional study - Chak Sing Lau; Weng Yee Chin; Amy Pui Pui Ng; Eric Yuk Fai Wan; Julie Chen (BMJ Open)
Objective To estimate the prevalence and severity of burnout and explore the factors associated with burnout among Hong Kong medical graduates up to 20 years post-graduation.Design Cross-sectional survey.Setting Hong Kong.Participants Doctors who graduated from the University of Hong Kong between 1995 and 2014.Primary and secondary outcome measures Burnout as measured by the Copenhagen Burnout Inventory (CBI), alcohol consumption as measured by the Alcohol Use Disorders Identification Test Version C, lifestyle behaviours (hours of sleep and work, exercise, smoking, substance use), career satisfaction and sociodemographic characteristics were obtained using paper or online questionnaires.Results Response rate was 30.9% (496/1607). Prevalence of CBI burnout was 63.1% (personal), 55.9% (work-related) and 35.4% (patient-related). The mean CBI subscale scores were 57.4±21.4 (personal), 48.9±7.4 (work-related) and 41.5±21.8 (client-related). Factors associated with personal and patient-related burnout included age (coeff −0.437, 95% CI −0.779 to −0.095 and coeff −0.596, 95% CI −0.965 to −0.228, respectively), practice setting (coeff −5.759, 95% CI −10.665 to −0.853 and coeff −5.317, 95% CI −10.602 to −0.032, respectively) and regular exercise (coeff −6.855, 95% CI −11.102 to −2.608 and coeff −6.769, 95% CI −11.333 to −2.205, respectively). Gender (coeff 5.1, 95% CI 1.382 to 8.818), average hours of sleep per night (coeff −5.200, 95% CI −7.139 to −3.262) and work hours per week (coeff 0.226, 95% CI 0.099 to 0.353) were associated with personal burnout only. No factors were significantly associated with work-related burnout.Conclusion Burnout is highly prevalent among Hong Kong medical graduates. Younger doctors, women and those working in the public sector appear to be at higher risk for burnout and may benefit from targeted interventions. Policymakers and healthcare authorities should consider measures to help reduce burnout by enabling adequate sleep, reducing work hours and encouraging exercise.